ANALYSIS OF THE EFFECTIVENESS OF TOURISM OBJECT RETRIBUTION REVENUE AS A SUPPORTING SOURCE OF REGIONAL ORIGINAL REVENUE IN MAMASA REGENCY - Puspa Alma; Baso Amang; Asriani Junaid (Magister Akuntansi - Universitas Atma Jaya Makassar, 2026)
Abstract: This study examines the effectiveness of tourism attraction levy revenue in supporting Local Own-Source Revenue (PAD) in Mamasa Regency and identifies factors affecting revenue target achievement. A qualitative phenomenological approach was employed, using interviews, observations, documentation, and secondary data from the Mamasa Regency Tourism Office. The findings show that tourism levy revenue effectiveness remains low, as revenue realization has not reached the established targets despite annual growth. Key challenges include inadequate tourism facilities, limited promotion, low tourist arrivals, ineffective levy management, and insufficient human resources. Liawan Waterfall contributed the highest levy revenue among the tourist attractions studied. The study concludes that improving levy revenue effectiveness requires infrastructure development, enhanced service quality, digitalization of levy collection, stronger tourism promotion, and collaboration among stakeholders. These efforts are expected to increase tourist visits and strengthen the contribution of the tourism sector to local revenue in Mamasa Regency.